1995
DOI: 10.1016/0165-2427(94)05379-7
|View full text |Cite
|
Sign up to set email alerts
|

Isotype-specific antibody responses to bovine herpesvirus 1 in sera and mucosal secretions of calves after experimental reinfection and after reactivation

Abstract: Isotype-specific antibody responses to bovine herpesvirus 1 (BHV1) were measured in sera, nasal, ocular and genital secretions of calves that were reinfected with BHV1 and 6 weeks later treated with corticosteroids to reactivate putative latent virus. After reinfection and after reactivation, no BHV1-specific IgM antibody response was detected. The serum IgA response was only transiently detectable after reinfection and again appeared rapidly after reactivation in most calves. Most calves showed an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(15 reference statements)
2
8
1
Order By: Relevance
“…The findings reported here support the inclusion of testing for FMDV-specific IgA in serum in addition to mucosal fluid samples. Indeed, Madic and colleagues [63] have suggested that serum IgA was the most sensitive indicator of bovine herpesvirus 1 reinfection or reactivation. We found greater individual variation in the IgA responses in serum than in probang samples in the 'carrier' cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported here support the inclusion of testing for FMDV-specific IgA in serum in addition to mucosal fluid samples. Indeed, Madic and colleagues [63] have suggested that serum IgA was the most sensitive indicator of bovine herpesvirus 1 reinfection or reactivation. We found greater individual variation in the IgA responses in serum than in probang samples in the 'carrier' cattle.…”
Section: Discussionmentioning
confidence: 99%
“…IgA levels were low at 180 days pi, but reactivation led to a new IgA peak. IgA was also found to rise upon reactivation by others (8). Therefore, the presence of elevated levels of IgA, concomitant with elevated IgG1 and IgG2 and absence of IgM may provide additional evidence to indicate that calves have been through a recent reactivation process.…”
mentioning
confidence: 61%
“…During reactivation, no rise in IgM levels was detected, following an expected profile (5, 8). This may be useful for distinguishing the phases of infection, in that the analysis of the IgM profile can provide a way to differentiate acute infections from reactivation.…”
mentioning
confidence: 79%
See 2 more Smart Citations